Testing the motor proficiency barrier hypothesis for physical activity and weight status - Lopes, Vitor P. (2018)
Motor competence (MC) is associated with physical activity (PA) and a healthy weight in childhood years. The purpose was to test a MC proficiency barrier (PB), below which children would not achieve enough PA levels to be healthy. Cut-off values in KTK test results were determined with ROC analysis using a cross-sectional sample of 734 (353 girls) 10 year-old children. These cut-off values were subsequently used to define two different groups (high and low MC) in a short term longitudinal sample of 217 (118 girls). MC, PA, and BMI were assessed at baseline (12.1±0.4 years-old) and after two years (14.6±0.3 years-old). RM ANOVA (2x2) were performed to analyze the difference in BMI, sedentary time (ST) and moderate-to-vigorous PA (MVPA) changes between low and high MC at baseline. 2 X 2 Chisquare tests were conducted to test the independence of low and high MC on weight status, PA, and ST. Logistic regressions were conducted to find if the odds of being obese, sedentary, or active were different according PB status at baseline. The MC cut-off of 79 and 75 for girls and boys respectively, were used as PB. In both boys and girls there were no significant changes in BMI, ST, and MVPA, according to MC level. PB effectively predicted significant different classifications on weight status, and combined weight status and MVPA, at both baseline and follow-up. The probability of being overweight two years in the future, when below the hypothesized PB at baseline was 2.78 higher than when above the PB.